Imunomarcação da OPG e RANKL no reparo ósseo após a cirurgia de elevação do seio maxilar com Bio-Oss - Rodríguez Sánchez, Maria Del Pilar [UNESP] (2015)
The prosthetic rehabilitation with dental implants has become a common treatment, to replace missing teeth, after that the alveolar process go through the natural process of resorption, resulting ridges with poor bone volume for a good surgical and prosthetic planning. Sinus lifting technique, by the lateral window technique is well documented, using autogenous bone grafts, xenogenous, homogenous or alloplastic materials. The aim of this research was to assess new bone formation and the events of bone remodeling after maxillary sinus lifting surgery using Bio-Oss® associated with autogenous bone or isolated by immunolabeling of the new members of necrosis tumoral factor Osteoprotegerin (OPG) and the Receptor Activator for Nuclear Factor kβ (RANKL). Twenty-five patients with good general health status were selected to perform reconstructive surgeries of the posterior maxilla and later performed the installation of osseointegrated dental implants in a second surgical time. Maxillary sinus were divided in 3 groups, depending on the graft as follow: Group B: Bio-Oss®; Group BA: 1;1 Bio-Oss® + bone graft; Group A: Autogen bone graft. Biopsies of implant placement areas were collected for histometric and immunohistochemical assesses. Histometric data were statistically analyzed by ANOVA and Tukey parametric test, to establish differences among groups. The immunohistochemical assess was qualitative ordinal, giving scores to the protein stained. Histologic findings showed new bone formation in all groups, particles of Bio-Oss were observed on groups Bio-Oss and Bio-Oss-autogenous bone graft 1;1, surrounded by new bone. There were significant differences among groups related to new bone formation (ANOVA p=0.002), pointed out more new bone formation on the autogenous group. Intense immunolabeling was observed in OPG and RANKL...